2000
DOI: 10.3171/spi.2000.93.1.0053
|View full text |Cite
|
Sign up to set email alerts
|

Surgical evaluation and management of lumbar synovial cysts: the Mayo Clinic experience

Abstract: Object. The authors report a retrospective analysis of 194 patients surgically treated at their institutions for symptomatic lumbar synovial cysts from January 1974 to January 1996. Methods. Patient characteristics including age, sex, symptoms, signs, and preoperative neuroimaging studies were reviewed. Surgical procedures, complications, results, and pathological findings were cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
273
0
11

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 162 publications
(296 citation statements)
references
References 40 publications
12
273
0
11
Order By: Relevance
“…21) These lesions usually present with common symptoms of radiculopathy, neurogenic claudication, myelopathy, neurological deficit, and even cauda equina syndrome. 18,23) Here we discuss our experience with various types of lumbar spinal synovial cyst, including the evaluation, treatment modalities, and pathologies in the differential diagnosis of lumbar radiculopathy, especially in older patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…21) These lesions usually present with common symptoms of radiculopathy, neurogenic claudication, myelopathy, neurological deficit, and even cauda equina syndrome. 18,23) Here we discuss our experience with various types of lumbar spinal synovial cyst, including the evaluation, treatment modalities, and pathologies in the differential diagnosis of lumbar radiculopathy, especially in older patients.…”
Section: Introductionmentioning
confidence: 99%
“…3,7) Magnetic resonance (MR) imaging has increased detection compared to older methods of myelography and computed tomography (CT) in patients with low back pain and radicular pain. 18,28) The overall prevalence of anterior and posterior facet joint cysts are 2.3% and 7.3%, respectively, and back pain is the primary symptom for cysts located posterior to the facet joint, possibly because the ligamentum flavum (LF) acts as a mechanical barrier against the formation of anterior cysts. 7) Synovial cysts within the lumbar spinal canal are usually classified as synovial cyst, ganglion cyst, posterior longitudinal ligament (PLL) cyst, or LF cyst based on their location, 9) origin, 1,34) and pathologic features.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, primary synovial cysts are typically observed in the mobile segments of the lumbar spine where spondylosis most frequently occurs. The most common sites, in descending order of incidence, are L4-5 and L3-4 [9,20]. These lumbar levels appear in association with the degeneration of the facet joint and are probably caused by repetitive trauma and a microinstability that produce areas of focal weakness in the facet capsule.…”
Section: Discussionmentioning
confidence: 99%
“…A few reports found that low back pain preceded radicular symptoms in most patients [9,11]. Because most intraspinal facet cysts are associated with spinal column arthropathy, non-localised back pain is usually not attributable solely to the cyst.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation